Feed depredation by european starlings - Parsons, G.L.; Shelor, M.K.; Depenbusch, Brandon E.; Drouillard, James S.; Lee, Charles D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
European starlings (Sturnus vulgaris) were first introduced to the United States in the late 1800s. It is believed that the starlings were imported from Europe and released in New York City’s Central Park so that all of the birds mentioned in Shakespeare’s works would inhabit the new country. For the next 50 years, the starling population grew exponentially; by 1942, starlings had spread to the West Coast. Starlings are not considered migratory and remain in the same general area year round; however, some may migrate several hundred miles. During much of the year, the inconspicuous starlings disperse into small flocks and feed on seeds, fruits, and insects. During winter months, starlings form flocks of several hundred up to 750,000 birds that share feeding and roosting sites. These large flocks prefer to roost in coniferous trees, which provide protection from wind and adverse weather conditions. Previous research has documented that a 3-oz starling consumes nearly 2 lb of feed in a 30-day period. Commercial feedlots have been infested with large populations of starlings during winter months. The attraction to feedlots is due to open feed bunks that provide a convenient source of feed. Currently, there are limited means for controlling starlings in feedlots. The objective of our experiment was to compare susceptibility of different rations to depredation by starlings.
Keywords: Beef; Cattle; European starlings